AEROBIC EXERCISE TRAINING AS A POTENTIAL THERAPY FOR PARKINSON’S DISEASE PATIENTS: A LITERATURE REVIEW - Sinurat, Ireene Hillary Artauli; Juhanna, Indira Vidiari (Sport and Fitness Journal, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that exhibits motor and non-motor symptoms. The management of PD consists of pharmacotherapy and surgical management. However, the clinical improvement of pharmacotherapy is still inconsistent. Aerobic exercise provides a restorative and protective benefit by supporting synaptogenesis and angiogenesis, oxidative stress inhibition, and increasing mitochondrial function. It can be a complementary treatment to pharmacotherapy management. We aimed to describe the effect of aerobic exercise on Parkinson’s disease through a literature review. Literature searching was performed using the keywords (aerobic exercise) AND (Parkinson’s disease) to obtain eligible articles. The literature search was performed in the PubMed database. The findings in the included articles were reviewed and described narratively. Aerobic exercise has a protective effect on the nigrostriatal dopaminergic system and could improve symptoms of PD including somatomotor and non-motor symptoms. The mechanism of aerobic exercise and its effect on neuroprotection includes the increased release of neurotrophic factors such as brain-derived neurotrophic factor (BDNF) and glial cell-derived neurotrophic factor (GDNF), increased serum urate, regulating turnover of dopamine, and upregulating the transcriptional regulator peroxisome proliferator-activated receptor gamma (PPAR?) coactivator 1? (PGC1?). Aerobic exercise can improve balance, gait velocity, stride/step length, and other motor functions in patients with PD. Improvement of cadence and quality of life is still inconclusive following aerobic exercise in patients with PD.